YOLO - a robot that will make your creativity BOOM - Alves-Oliveira, P.; Chandak, A.; Cloutier, I.; Kompella, P.; Moegenburg, P.; Pires, A. (13th Annual ACM/IEEE International Conference on Human Robot Interaction, 2018)
One of the functions of creativity is to improve society. Creativity is a skill that can be trained and has proven benefits for the professional and personal development of individuals. Yet, a paradox exists: despite seeking individuals with a greater creative potential, society lacks systems that nurture the development of this skill. Technological advances arrive with the potential to develop solutions that support the development of creative skills. In this proposal, we introduce YOLO, a social robot that acts as a tool for developing creativity in children. YOLO resembles a robotic toy with a life of its own, developed specially for children, and envisioned to be used during playtime. YOLO can boost new ideas for children’s invented stories, by making use of minimalist behaviors that are meant for creativity expansion and social connectedness. We present the design and fabrication processes of YOLO, including examples of potential scenarios of use. With YOLO we aim to demonstrate a potential scenario in which autonomous robots can be used to promote social good.